2022
DOI: 10.1200/jco.2022.40.16_suppl.e24009
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing immunotherapy adverse events in elderly cancer patients.

Abstract: e24009 Background: Immunotherapy (IT) has cemented itself as a mainstay in cancer treatment, especially in those with late stage malignancies. Generally, these agents are well tolerated, but there is a known association with immune-related adverse events (iRAE). Due to an underrepresentation of elderly patients in clinical trial data, it is valuable to understand the tolerance of these agents. The primary objective of our study was to evaluate for an association between older age, defined as age 75 and above,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The comprehensive therapies of the elderly with end-stage tumor include the principle of individualization, identifying patient-specific vulnerabilities, and predicting the potential unexpected risks of various therapies [ 10 ]. Data related to 229 elderly patients with end-stage cancer in a retrospective study by Sganga [ 11 ]et al showed: elderly patients with a high number of comorbidities; high indicators of comprehensive care; a greater need for access to palliative care due to the complexity of the co-existing social, psychological, and medical needs of centenarians.…”
Section: Discussionmentioning
confidence: 99%
“…The comprehensive therapies of the elderly with end-stage tumor include the principle of individualization, identifying patient-specific vulnerabilities, and predicting the potential unexpected risks of various therapies [ 10 ]. Data related to 229 elderly patients with end-stage cancer in a retrospective study by Sganga [ 11 ]et al showed: elderly patients with a high number of comorbidities; high indicators of comprehensive care; a greater need for access to palliative care due to the complexity of the co-existing social, psychological, and medical needs of centenarians.…”
Section: Discussionmentioning
confidence: 99%